Factors that generate fear of childbirth: An integrative review - Luciana Jares Travancas; Octavio Muniz da Costa Vargens (Universidade Federal de Santa Maria, 2020)
Objective: to identify, in the scientific evidence, factors considered by women to trigger fear of childbirth. Method: an integrative review with the following question: What factors do women consider triggering or influencing fear of childbirth? Searches were carried out in the Portals of the Virtual Health Library and in the Journals Portal of the Coordination for the Improvement of Higher-Level Personnel, through combinations of descriptors and keywords adhering to the theme. In response, 27 articles were found using the following inclusion criteria: articles in English, Portuguese or Spanish, in full, published and indexed between 2008 and 2018. Results: the following stood out as factors that trigger fear: perceptions related to vaginal delivery, fears related to the choice of cesarean section, and fear of inadequate care by the professionals, among other factors. Conclusion: giving pregnant women back the power over their bodies, strength and ability to give birth naturally without fear, is a challenge faced by Nursing care.